Special Cement-Based Grouting Material for Subway Structure Repair During Operation Performance Sensitivity Analysis - Wei Song; Xiaokai Niu; Zhitian Xie; He Wang; Jie Su; Chentao Xu (Buildings)
This study uses ordinary Portland–sulfate–silicate composite cement as the matrix and investigates the effects of water–cement ratio, HPMC dosage, and PCS dosage on the performance of specialized grouting materials for subway structure repair during operation through single-factor experiments and orthogonal experiments. Multifactorial variance analysis was employed to quantitatively evaluate the sensitivity of each factor and their interactions to slurry flowability, setting time, anti-dispersibility, and compressive strength. The results show that the water–cement ratio is the most critical factor affecting the performance of the grouting material, with extremely significant impacts on all performance indicators; HPMC dosage significantly affects flowability, setting time, and anti-dispersibility; PCS dosage primarily influences 2 h compressive strength; the interaction between water–cement ratio and HPMC dosage has a significant impact on anti-dispersibility. Principal component analysis revealed the trade-off relationship between flowability, setting time, and strength. The study established a sensitivity ranking for the performance of specialized grouting materials: water–cement ratio > HPMC dosage > PCS dosage > interaction, providing a theoretical basis and methodological reference for the formulation optimization of specialized grouting materials for subway structure repair during operation.